Localized Adult Ewing Sarcoma: Favorable Outcomes with Alternating Vincristine, Doxorubicin, Cyclophosphamide, and Ifosfamide, Etoposide (VDC/IE)‐Based Multimodality Therapy. (26th May 2017) - Pretz, Jennifer L.; Barysauskas, Constance M.; George, Suzanne; Hornick, Jason L.; Raut, Chandrajit. P.; Chen, Yen-Lin E.; Marcus, Karen J.; Choy, Edwin; Hornicek, Francis; Ready, John E.; DeLaney, Thomas F.; Baldini, Elizabeth H.
Abstract: Background: In children with localized Ewing sarcoma (ES), addition of ifosfamide and etoposide to cyclophosphamide, doxorubicin, and vincristine (VDC/IE) improved 5‐year overall survival (OS) to 70%–80%. Prior to delivery of VDC/IE in adults, 5‐year OS was <50%. We reviewed our institutional outcomes for adults with ES who received VDC/IE‐based treatment. Materials and Methods: Between 1997–2013, 67 adults with localized ES were treated with curative intent. Local recurrence‐free survival (LRFS), progression‐free survival (PFS), and OS were determined using Kaplan‐Meier method; comparisons were assessed with log‐rank. Proportional hazard models were used to determine predictive factors. Results: All patients received VDC/IE (median 14 cycles.) Local therapy was surgery for 33, radiation therapy for 17, or both for 17. Median follow‐up for living patients was 5.2 years. Six patients had disease progression on therapy. Site of first failure was local for three, local and distant for two, and distant for ten. Five‐year LRFS was 91%; 5‐year LRFS was 96% for nonpelvic disease and 64% for pelvic disease ( p  = .003). Five‐year PFS was 66%, and 5‐year OS was 79%. On multivariate analysis, pelvic site had a 3.3 times increased risk of progression ( p  = .01). Conclusion: Survival for adults with localized ES treated with VDC/IE‐based multimodality therapy appears to be better than historical data and similar to excellent outcomes in children. Pelvic site of disease remains a predictor of worse outcome. Given the paucity of literature for adult ES, these data help validate VDC/IE‐based therapy as an appropriate treatment approach for this rare disease in adults. Abstract : Although typically considered a pediatric disease, Ewing sarcoma can occur adults. Current standard treatment for localized Ewing sarcoma is a multimodality approach, combining chemotherapy and local therapy consisting of surgery and/or radiation therapy. This article evaluates outcomes for adults with localized Ewing sarcoma treated exclusively with cyclophosphamide, doxorubicin, and vincristine followed by ifosfamide and etoposide in combination with local therapy.